Fensterbierscheiben in the Pena National Palace collection – chemical and iconographic relations. (6th September 2016) - Coutinho, I.; Berger, F.; Rodrigues, A.; Coutinho, M. L.; Machado, A.; Alves, Luis C.; Vilarigues, M.
Abstract : The stained‐glass collection from the Pena National Palace (Sintra, Portugal) includes around 130 'rural panels', also known as Fensterbierscheiben, that were produced between the 16th and 19th centuries. The aim of this investigation is to characterise the glass composition of this collection of Fensterbierscheiben and relate it with the iconographic research made on these panels, in order to establish possible provenance of production. This is the first study on Fensterbierscheiben, where the chemical information of the glass is considered and related with historical information. The micro‐energy dispersive X‐ray fluorescence allowed performing non‐invasive analysis, mostly performed in situ . Micro‐particle‐induced X‐ray emission analysis was performed on the cross section of a small group of fragmented panels for obtaining quantitative chemical composition of the glass. Through the analysis of the colourless glass, and the comparison of micro‐energy dispersive X‐ray fluorescence and micro‐particle‐induced X‐ray emission data, it was concluded that the majority of the panes have a high lime low alkali glass composition. Furthermore, the Fensterbierscheiben panes form a cohesive group in terms of composition, suggesting that they were all manufactured with raw materials from the same region. This study also allowed one to observe the chronological evolution in terms of treatments applied to the used raw materials. Copyright © 2016 John Wiley & Sons, Ltd.